Paclitaxel‐coated balloon in the treatment of recurrent dysfunctional arteriovenous access, real‐world experience and longitudinal follow up. Issue 12 (29th April 2019) - Phang, Chee Chin; Tan, Ru Yu; Pang, Suh Chien; Tan, Chee Wooi; Teh, Swee Ping; Cheng, Rui‐Wern; Kho, Yu Xuan; Chong, Tze Tec; Gogna, Apoorva; Foo, Wai Yin; Tan, Chieh Suai
ABSTRACT: Aim: Dysfunctional arteriovenous (AV) access remains a significant cause of morbidity and hospital admission for patients with end stage renal failure on haemodialysis. This study was performed to evaluate the impact of paclitaxel‐coated Balloon (PCB) on the patency of AV access with recurrent stenoses. Methods: We retrospectively studied haemodialysis patients who presented to our centre with recurrent AV access dysfunction and compared intervention‐free patency using plain balloon versus PCB. Results: A total of 147 patients were followed up longitudinally. Intervention‐free patency was better following PCB compared to previous intervention using plain balloons (6.4 ± 5.8 versus 4.0 ± 3.7, P  < 0.01). The 3‐ and 6‐month patency rates after PCB were significantly better compared to standard plain angioplasty balloon: 69.4% versus 52.4%, P  < 0.01 and 42.9% versus 15.6%, P  < 0.01 respectively. Kaplan–Meier survival analysis of circuit patency demonstrated the superiority of PCB over plain balloon angioplasty in both arteriovenous fistula and arteriovenous graft ( P  < 0.01 and P  = 0.01 respectively) although the patency of arteriovenous fistula remained significantly better than arteriovenous graft following interventions with PCB ( P  < 0.01). Age of AV access and the number of previous interventions were found to be significant predictors of patency following PCB intervention. Conclusion: Arteriovenous access intervention with PCB was shown to be superior compared to plain balloon in the treatment of both non‐thrombosed and thrombosed AV accesses in our multi‐ethnic population. SUMMARY AT A GLANCE: This retrospective study compared arteriovenous access intervention‐free patency rates between plain balloon and paclitaxel‐coated balloon (PCB) angioplasty after intervention. PCB is shown to be superior to plain balloon angioplasty.